Primary healthcare workers’ COVID-19 infection status following implementation of adjusted epidemic prevention and control strategies: a cross-sectional study in Jiangsu, China - Lu, Beier; Ma, Rongji; Xu, Jinshui; Zhang, Yongjie; Guo, Haijian; Chen, Hualing; Miao, Pengcheng; Qian, Yongkang; Xu, Biyun; Shen, Ya; Chen, Bingwei (Frontiers in Public Health, 2023)
In times of epidemic outbreaks, healthcare workers (HCWs) emerge as a particularly vulnerable group. This cross-sectional study endeavors to assess the COVID-19 infection rate among the primary HCWs in Jiangsu Province subsequent to the implementation of adjusted epidemic prevention and control strategies.Methods: From January 17 to February 2, 2023, an extensive survey was conducted among primary HCWs in Jiangsu Province, employing a self-designed questionnaire. Logistic regression analysis was utilized to identify the factors associated with COVID-19 infection.The overall infection rate among primary HCWs stood at 81.05%, with a 95% confidence interval (CI) of 80.61%-81.48%. Among those afflicted, cough, fatigue, and fever emerged as the three most prevalent symptoms, each with an incidence rate exceeding 80%. In the context of multivariate logistic regression, an elevated risk of COVID-19 infection was observed in correlation with female gender (adjusted odds ratio [aOR]=1.12, 95%CI: 1.04-1.21), possessing a bachelor's degree or higher (aOR=1.32, 95%CI: 1.23-1.41), accumulating over 10 years of work experience (aOR=1.28, 95%CI:1.11-1.47), holding a middle-level cadre position (aOR=1.22, 95%CI: 1.11-1.35), assuming the role of a unit leader (aOR=1.30, 95%CI: 1.11-1.54), and working in a fever clinic for 1 to 10 days per month (aOR=1.42, 95%CI: 1.29-1.57). Conversely, advanced age (aOR=0.76, 95%CI: 0.70-0.82), being underweight (aOR=0.78, 95%CI: 0.69-0.90), current smoking (aOR=0.64, 95%CI: 0.57-0.71), receiving 4 doses of COVID-19 vaccine (aOR=0.49, 95%CI: 0.37-0.66), and pregnancy or perinatal status (aOR=0.85, 95%CI: 0.72-0.99) were associated with a diminished risk of infection.Following the implementation of adjusted policies, a substantial proportion of primary HCWs in Jiangsu province contracted COVID-19. Female gender and younger age emerged as risk factors for COVID-19 infection, while no discernible link was established between professions and COVID-19 susceptibility. The receipt of COVID-19 vaccines demonstrated efficacy in curtailing the infection rate, underscoring the significance of bolstering prevention knowledge and heightening selfprotective awareness among primary HCWs.